2014
DOI: 10.1152/ajpheart.00894.2013
|View full text |Cite
|
Sign up to set email alerts
|

PKC-mediated toxicity of elevated glucose concentration on cardiomyocyte function

Abstract: While it is well established that mortality risk after myocardial infarction (MI) increases in proportion to blood glucose concentration at the time of admission, it is unclear whether there is a direct, causal relationship. We investigated potential mechanisms by which increased blood glucose may exert cardiotoxicity. Using a Wistar rat or guinea-pig isolated cardiomyocyte model, we investigated the effects on cardiomyocyte function and electrical stability of alterations in extracellular glucose concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(56 citation statements)
references
References 41 publications
8
48
0
Order By: Relevance
“…In the present study, we have addressed this hypothesis by investigating the link between acute elevations in glucose concentration and changes in vascular function. We present data demonstrating for the first time that a glucose concentration‐dependent increase in vessel contraction is mediated by the DAG‐ and Ca 2+ ‐sensitive PKCα and PKCβ isoenzymes, as also recently shown in cardiomyocytes (Sims et al , ). This mechanism appears to be common to rat mesentery, porcine coronary and human internal mammary arterial tissues.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, we have addressed this hypothesis by investigating the link between acute elevations in glucose concentration and changes in vascular function. We present data demonstrating for the first time that a glucose concentration‐dependent increase in vessel contraction is mediated by the DAG‐ and Ca 2+ ‐sensitive PKCα and PKCβ isoenzymes, as also recently shown in cardiomyocytes (Sims et al , ). This mechanism appears to be common to rat mesentery, porcine coronary and human internal mammary arterial tissues.…”
Section: Introductionsupporting
confidence: 85%
“…Acute elevations of extracellular glucose have also been shown to have deleterious effects on the electrical properties of isolated cardiomyocytes, causing a marked prolongation of action potential duration (Hreiche et al, 2009) and subsequent QT prolongation, which is suggested to be pro-arrhythmic (Marfella et al, 2001;Gordin et al, 2008). Our own recent findings suggest a similar DAG/Ca 2+ -PKC isoenzyme-dependent dysregulation of electrical signalling in cardiac tissue (Sims et al, 2014). The findings of the current study provide evidence for a common potential mechanism through which elevated glucose may exert direct deleterious effects on cardiovascular function with similar DAG/Ca 2+ -PKC isoenzyme-dependent mechanisms being evident in both heart and vasculature.…”
Section: Figurementioning
confidence: 72%
“…The protocol for isolation of cardiomyocytes was as described previously ( 26 ). Briefly, the whole heart was rapidly excised and placed into cold, nominally Ca 2+ -free Tyrode's solution (NT).…”
Section: Methodsmentioning
confidence: 99%
“…Normal physiological saline (NPS), used in all experiments on living megakaryocytes, consisted of 145 mM NaCl, 5 mM KCl, 1 mM MgCl 2 , 1 mM CaCl 2 , 10 mM HEPES, 10 mM glucose, pH 7.35 with NaOH. Ventricular myocytes were prepared using retrograde perfusion via a Langendorff cannula as described in detail elsewhere 69 . Briefly, the heart was rapidly excised, placed into cold Ca 2+ -free Tyrode’s solution (0CaTS; 5 mM KCl, 135 mM NaCl, 0.33 mM NaH 2 PO 4 , 5 mM Na Pyruvate, 10 mM HEPES, 15 mM mannitol, 5 mM glucose, 1 mM MgCl 2 ) and rapidly cannulated via the aorta.…”
Section: Methodsmentioning
confidence: 99%